Decision Support System Untuk Menetapkan Daya Listrik Bagi Pelanggan PLN - Fauziah, Sifa; Muryani, Sri (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2019)
The need for electrical energy is very dominant for humans, starting from the needs in the household, government business, home industry to large industries and all other aspects of life, now means that the availability of electricity is very important and very influential in increasing the socio-economic quality growth rate society in general. A PLN user to find out how much lamp power is needed in a room judging subjectively that is still in accordance with his own wishes. This writing makes the application using fuzzy logic to find out how much electrical power is used in an appropriate manner. To make it easier for a PLN user to determine the electrical power that is in accordance with the requirements, the author makes the application using fuzzy logic. The programming language used is visual basic. The benefit of this writing is to help a PLN user to optimize electric power so that it can save energy.